Media Choice and Public Participation in the Budget Making Process for Nyeri County - Ogoti, Lucy; Mberia, Hellen; Ndavula, John (International Journal of Communication and Public Relation, 2024)
Purpose: The aim of the study was to determine the effect of Media Choice on Public Participation in the Budget Making Process in Nyeri County. Methodology: The study population constituted all the residents operating and living in Nyeri County, Nyeri County Government officials and leaders from both the County Executive and County Assembly. The study applied a descriptive study design and used both primary and secondary data that was obtained from public participation reports, publications, and interviews with county government officials, budget committee members and questionnaires to the MCAs, residents, staff of the County Assembly. Stratified random sampling was used to select and identify respondents from Nyeri County residents' attendees in public participation fora and a further random sampling to obtain respondents from the Wards. Strata and purposive sampling was used to get key informants from the County Executive and County Assembly. A sample size of 72 general respondents and 12 key informants was used. Both quantitative and qualitative data was collected using a study questionnaire and interview guides respectively. Qualitative data was represented using study themes or goals and was discussed in narrative. The quantitative data was sorted and analyzed using the Statistical Package for Social Sciences (SPSS) version 25. The findings were presented using tables and graphs Findings: A regression correlation analysis of the data showed that the independent variables (social media =0.044, for print media = 0.047) were significant with p values of less than 0.05 - the predetermined significance level - to imply that the results were statistically significant. The p value for radio station was 0.326, greater than 0.05, thus not significant in its effect on public participation in the budget making process in the County Government of Nyeri. From the data collected, great importance was placed on vernacular and community radio stations which are potential channels for communicating pertinent information on the budget making process. The research found out other factors that determine effectiveness of public participation to include public's awareness of its rights, individual understanding of the processes, and level of education and prevailing support infrastructure. Unique Contribution to Theory, Practice and Policy: The Medium Theory and Arnstein's Ladder of Citizen Participation Model informed the study variables and approach. Further research is recommended to explore other variables. The study findings will help planners and implementers at the County level when setting out to engage the public for their participation in the County's development agenda. .